Detection of Leptospira spp. in kidney tissues isolated from rats in the Napu and Bada Highlands of Poso District, Central Sulawesi Province - Gunawan Gunawan; Tri Wibawa; Mahardika Agus Wijayanti; Hayani Anastasia (Jurnal Vektor Penyakit, 2020)
Leptospirosis is still a global health problem because it affects human health in rural and urban areas, both in industrialized and developing countries. The aim of the study was to detect Leptospira spp. bacteria in kidney tissues isolated from rats in the Napu and Bada Highlands of Poso District, Central Sulawesi Province. Kidneys sample from 63 rats were collected from Napu and Bada Highlands of Poso District, Central Sulawesi Province in MayJune 2018. Polymerase Chain Reaction (PCR) was used to detect Leptospira. The molecular characterizations were conducted based on the 16SrRNA and LipL32 genes. Data were analyzed descriptively to describe the presence of pathogenic Leptospira DNA. Analysis phylogenetic was performed using MEGA 6.2 software. A total of 63 rats was successfullycaught during the study consisting of males and female for 36 (57.1%) and 27 (42.9%), respectively. The species of rats were R. exulans, R. tanezumi, R. argentiventer, R. norvegicus, M. Musculus, Paruromys dominator, Maxomys sp., and Rattus sp. The pathogenic of Leptospira DNA was detected in rats with R. argentiventer and Paruromys dominatorspecies using the 16S rRNA and LipL32 gene. Sample sequences using LipL32 target gene is a close similarity with L. interrogans serovar Hardjo, serovar Autumnalis, Lai, Icterohaemorrhagiae, Balico, Grippotyphosa, Mini, Canicola, Hebdomadis; L. noguchii serovar Pomona and L. kirschneri whereas the sample sequence using 16S rRNA targetgene showed similarity with L. interrogans serovar Canicola, Copenhagen, Autumnalis, Pyrogenes, Javanica, Icterohaemorrhagiae, Manilae, Bratislava, Linhae, Hebdomadis, and L. kirschneri serovar Grippotyphosa. The PCR method with the target gene 16SrRNA and LipL32 are able to detect Leptospira spp. in rats R. argentiventer and P. dominator species Keywords: Leptospira, 16S rRNA, LipL32, PCR, Kidney’s Rat Leptospirosis masih merupakan masalah kesehatan global karena mempengaruhikesehatan manusia di daerah pedesaan dan perkotaan, baik di negara industri maupun mnegara berkembang. Tujuan penelitian adalah untuk mendeteksi bakteri Leptospira spp di jaringan ginjal dari tikus di Dataran Tingi Napu dan Bada Kabupaten Poso, Provinsi Sulawesi Tengah. Ginjal tikus sebanyak 63 sampel dikoleksi dari Dataran Tinggi Napu dan Bada Kabupaten Poso, Provinsi Sulawesi Tengah pada bulan Mei – Juni 2018. PCR digunakan untuk mendeteksi Leptospira. Karakterisasi molekuler dilakukan berdasarkan gen 16SrRNA dan LipL32. Data dianalisis secara deskriptif untuk menggambarkan keberadaaN Leptospira yang patogenik. Analisis filogenetik dilakukan dengan menggunakan perangkat lunak Mega 6.2. Sebanyak 63 tikus berhasil ditangkap selama penelitian yang terdiri dari jantan dan betina, masing masing 36 ekor (75,1%) dan 27 ekor (42,9%). Spesies tikus adalah R. exulans, R. tanezumi, R. argentiventer, R. norvegicus, M. Musculus, Paruromys dominator, Maxomys sp, dan Rattus sp. DNA Leptospira patogenik terdeteksi pada tikus dengan spesies R. argentiventer dan Paruromys dominator menggunakan gen 16SrRNA dan LipL32 Sekuen sampel dengan target gen LipL32 menunjukkan kesamaan dengan L. interrogans serovar Hardjo, serovar Autumnalis, Lai, Icterohaemorrhagiae, Balico, Grippotyphosa, Mini, Canicola, Hebdomadis; L. noguchii serovar Pomona dan L. kirschneri. Sedangkan sekuen sampel dengan target gen 16S rRNA menunjukkan kesamaan dengan L. interrogans serovar Canicola,Copenhagen, Autumnalis, Pyrogenes, Javanica, Icterohaemorrhagiae, Manilae, Bratislava, Linhae, Hebdomadis, dan L. kirschneri serovar Grippotyphosa. Metode PCR dengan target gen 16SrRNA dan LipL32 mampu mendeteksi Leptospira spp. pada tikus dengan spesies R. argentiventer dan P. dominator. Kata kunci: Leptospira, 16S rRNA, LipL32, PCR, Ginjal Tikus